Compendium of ILRI research impacts and adoption, 1975-1998 - Thornton, Philip K.; Odero, A.N. (International Livestock Research Institute, 1998)
This document lists and summarises studies by ILRI (International Livestock Research Institute) and its predecessors, ILCA (International Livestock Centre for Africa) and ILRAD (International Laboratory for Research on Animal Diseases), on the adoption and impact of their research output. It will be updated regularly as old activities are completed and new ones are started. It says nothing directly about the adoption and impact of technologies developed by ILRI and national and international collaborators, although the summaries give a good approximation of such information, where it has been generated. To help the reader understand quickly the type of activity that each entry represents, the activities in the compendium are classified according to a simple typology and falls under one of the following classifications - Methodology Development; Ex Post Assessment; Ex Ante Assessment; Adoption; Impact Assessment; Economic Assessment, Environmental Assessment; and Social Assessment. In the compendium, activities appear in approximate chronological order of their starting date.